European Integration Processes in the EU GI System—A Long-Term Review of EU Regulation for GIs - Schober, Karola; Balling, Richard; Chilla, Tobias; Lindermayer, Hannah (Sustainability, 2023)
Prosciutto di Parma, Bavarian beer and Roquefort—Geographical Indications (GIs) have been systematically protected at the EU level for 30 years and are now an important part of the farm2fork strategy. The article analyses how the integration of the EU GI system can be explained from an institution and discourse theoretical perspective and ties in with the soft spaces debate. In doing so, scalar shifts in competence from a German perspective and the role of discursive spatial relations are examined in more detail. The empirical results are based on a mix of methods that includes the evaluation of secondary statistical data, document analyses, participant observation and expert interviews. The study shows that the European Commission (EC) is increasingly acting as a spokesperson for GIs, but that regional actors are also playing a more important role in implementation and enforcement. This development is fed by the influence of the agricultural policy instrument in terms of competition, but also consumer protection and trade policy. Overall, there are three development layers: protect and systematise, legitimise and expand and open and defend. A more independent development of the EU GI system as an instrument of quality policy and for the development of rural areas could give greater weight to the sustainability-relevant, environmental policy aspects currently demanded by society.
CRIS-Team Scopus Importer:2023-02-24
Keywords: CAP; European integration; Geographical Indications; institutional spillover; regional food; regional products; soft spaces

The EU food label 'protected geographical indication': Economic implications and their spatial dimension - Chilla, Tobias; Fink, Benedikt; Balling, Richard; Reitmeier, Simon; Schober, Karola (Sustainability, 2020)
This study analyses the economic effects of the EU policy on the protection of origin. The focus is on three types of food products with Protected Geographical Indication (PGI), whose reference areas are located in the Free State of Bavaria: Beer (Bayerisches Bier PGI), asparagus (Franken-Spargel PGI, Schrobenhausener Spargel PGI), and carp (Aischgrunder Karpfen PGI, Oberpfalzer Karpfen PGI). The study is based on secondary statistical analysis and a series of expert interviews. The results show positive effects on sales mainly for beer on international markets, and positive effects on price mainly for carp on the local and regional levels. All in all, we see that protection of origin stabilizes and supports the economic trajectory of its product. This study also shows that its economic effects vary widely: Firstly, price and sales effects are not automatic and differ in intensity; and secondly, the spatial dimensions of the economic effects exhibit different patterns. The primarily price-related effects at the local-regional level for carp (and to some extent for asparagus) are categorized as local effects (type A). The sales effect at the global level for beer is categorized as type B (export effect). Finally, this study postulates further potential forms of 'price and sales geographies'.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Asparagus; Bavaria; Beer; Carp; Economic effects; EU policy; Protected geographical indication; Protection of origin